2022
DOI: 10.1097/corr.0000000000001553
|View full text |Cite|
|
Sign up to set email alerts
|

Race, But Not Gender, Is Associated With Admissions Into Orthopaedic Residency Programs

Abstract: Background Orthopaedic surgery is one of the most competitive but least diverse surgical specialties, with everincreasing academic achievements (such as test scores) shown by applicants. Prior research shows that white applicants had higher United States Medical Licensing Exam (USMLE) Step 1 and Step 2 Clinical Knowledge scores as well as higher odds of Alpha Omega Alpha status compared with Black, Hispanic, and other applicant groups. Yet, it still remains unknown whether differences in application metrics by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 45 publications
6
70
0
Order By: Relevance
“…Based on these studies, it is plausible that poor rates of minority and female representation at every level of orthopaedics is a main driver of the similar trends found among HTPs in our study. 27 , 33 , 34 , 41 We did not find any differences between White and minority HTPs in terms of type of medical degree obtained, orthopaedic specialization, or number of years in practice, suggesting that a credential-based rationale for the low rates of minority representation is less likely. Increasing the percentage of minority providers within professional sports may have a number of benefits, including improved player-provider communication and trust.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Based on these studies, it is plausible that poor rates of minority and female representation at every level of orthopaedics is a main driver of the similar trends found among HTPs in our study. 27 , 33 , 34 , 41 We did not find any differences between White and minority HTPs in terms of type of medical degree obtained, orthopaedic specialization, or number of years in practice, suggesting that a credential-based rationale for the low rates of minority representation is less likely. Increasing the percentage of minority providers within professional sports may have a number of benefits, including improved player-provider communication and trust.…”
Section: Discussionmentioning
confidence: 72%
“…Female and minority representation in orthopaedic residency nationwide has also been studied. 7 , 28 , 33 Poon et al 32 studied orthopaedic demographic trends from 2005 to 2016 and found that among all the surgical specialties, orthopaedics consistently demonstrated some of the lowest rates of female and minority residents. Female resident representation increased from 10.9% to 14.4% during the study period (mean 13.3% over 10 years) but represented a significantly lower rate of increase compared with all surgical specialties, save urology.…”
Section: Discussionmentioning
confidence: 99%
“…Possible issues to be addressed include transparency in the selection process, holistic review of applications, bias in interviewing and ranking, application and/or interview caps, and match violations. 18,[30][31][32][33] This study is not without limitations. Using a survey has the risks of selection bias, which might limit the generalizability of the results.…”
Section: Discussionmentioning
confidence: 95%
“…Possible issues to be addressed include transparency in the selection process, holistic review of applications, bias in interviewing and ranking, application and/or interview caps, and match violations. 18,30-33…”
Section: Discussionmentioning
confidence: 99%
“…The findings on race in this study cry out not for more study, as is so often suggested, but for immediate action by residency programs, and perhaps those entities that accredit them. If this study [20] isn’t already the main item on every program’s residency-selection committee agenda for this month, it needs to be—so pass it along to the people you know who need to see it. When they look it over, I hope they’ll pay particular attention to the authors’ two-pronged recommendations [20], which make specific suggestions both about the application process and each program’s environment.…”
Section: Seth S Leopold MDmentioning
confidence: 99%